Perspective: leveraging review protocols to advance implementation science in support of older adults’ health equity - Bacsu, Juanita-Dawne; Pottle, Avery; Fehr, Florriann; Funk, Megan; Smith, Matthew Lee (Frontiers in Public Health, 2024)
Globally, there has been an increasing call for dissemination and implementation science to improve the health equity of older adults. However, improving the health equity of older adults requires methods that allow for an in-depth understanding of the existing research. While the value of review articles is widely recognized, the value of publishing review protocols is an emerging paradigm with great potential to advance implementation science and aging research. In this article, we propose that prior to review articles, review protocols are necessary as they provide a clear and comprehensive search strategy, which greatly enhances the quality and rigor of reviews. More specifically, we argue that review protocols are indispensable because they support: (1) a clearly defined and comprehensive search methodology; (2) reviewer feedback to mitigate potential issues; and (3) registration to reduce risk of research replication. Additionally, we propose three strategies to accelerate review protocols in implementation science to support older adults’ health equity.